Is What's "Trending" What's Worth Purchasing?: Insights from a National Study of Collection Development Librarians - Miles, Rachel A.; Sutton, Sarah; Konkiel, Stacy (My University, 2016)
New forms of usage data like altmetrics are helping librarians to make smarter decisions about their collections. A recent nationwide study administered to 13,000+ librarians at R1 universities shines light on exactly how these metrics are being applied in academia. This presentation will share survey results, including as-yet-unknown rates of technology and metrics uptake among collection development librarians, the most popular citation databases and altmetrics services being used to make decisions, and surprising factors that affect attitudes toward the use of metrics. This presentation will also offer actionable insights on how altmetrics are being paired with bibliometrics and usage statistics to form a more complete picture of “trending” scholarship that’s worth purchasing. Through sharing the survey results and opening up a discussion about the potential altmetrics hold for informing collection development, the presenters aim to provide a learning opportunity for attendees which will enhance their competencies for e-resource management, specifically, core competence for e-resource librarians 3.5, use of bibliometrics for collection assessment, and 3.7, identity and analyze emerging technologies.
Sutton, Sarah, Konkiel, Stacy, and Miles, Rachel. "Is What's 'Trending' What's Worth Purchasing? Insights from a National Study of Collection Development Librarians." NASIG Annual Conference 2016. (Albuquerque, NM). 10 June 2016. Presentation.
Keywords: altmetrics; bibliometrics; academic libraries; scholarly communication; research impact; research assessment